2021
DOI: 10.1002/adfm.202111026
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial and Ionic Modulation of Poly (Ethylene Oxide) Electrolyte Via Localized Iodization to Enable Dendrite‐Free Lithium Metal Batteries

Abstract: Solid polymer electrolytes (SPEs) make contact with highly reductive lithium (Li) metal anodes, forming the interphase that largely determines the battery performance. In this work, trace iodine doping in a poly(ethylene oxide) (PEO) electrolyte to achieve a stable interphase on Li metal surface for long battery cycling, is proposed. The triiodide ion (I3−) stemming from iodine additives can coordinate with the COC bond of PEO to enable the increased ionic conductivity of the SPE. The I‐doped interphase cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(75 citation statements)
references
References 56 publications
3
69
0
Order By: Relevance
“…Performance of various PEO-based SSEs. a) Schematic representations of ideal PEO-based SSEs; b) Temperature-dependent ionic conductivity of the PEO-based SSEs; c) Ionic conductivity of different content ND in the PEO-based SSEs at 30, 40, 50, 60, and 70 °C; d) Electronic conductivity of various PEO-based SSEs; e) LSV curves of various PEO-based SSEs; f) Comparison of the performance of PEO-based SSEs as per our data and previous reports [9,16,21,29].…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Performance of various PEO-based SSEs. a) Schematic representations of ideal PEO-based SSEs; b) Temperature-dependent ionic conductivity of the PEO-based SSEs; c) Ionic conductivity of different content ND in the PEO-based SSEs at 30, 40, 50, 60, and 70 °C; d) Electronic conductivity of various PEO-based SSEs; e) LSV curves of various PEO-based SSEs; f) Comparison of the performance of PEO-based SSEs as per our data and previous reports [9,16,21,29].…”
supporting
confidence: 73%
“…Besides, the Li + transference number (t Li + ) of ND-PEO SSE also showed a slight increasement under the mediation of NDs (Figures S6 and S7, Supporting Information). [9,16,21,29] According to previous works, high electronic conductivity of SSE will not only lead to growth of Li-metal dendrites insides the SSE, but also lead to degradation of PEO at high-voltage cathode side. Figure 1d shows the electronic conductivity of the three kinds of PEO-based SSEs.…”
Section: Resultsmentioning
confidence: 98%
“…The 1 H chemical shift of G4-I 2 is increased compared to that of pure G4, which could be attributed to the coordination between G4 and I 3 À through the polar À COCÀ group. [24,25] In general, I 2 could be reduced to I À by accepting electrons from the electron-donating substitute. In this case, the polar À COCÀ group as electron donor can reduce I 2 to I À , and the resultant I À reacts with neutral I 2 to form I 3 À polyanions.…”
Section: Methodsmentioning
confidence: 99%
“…Tao et al demonstrated localized iodization at the anode–electrolyte interface to promote interfacial lithium diffusion. 48 I 2 was added and reacted with PEO chains, enabling the spontaneous formation of a triiodide ion (I 3 − ). The compact and uniform iodine-containing SEI layer contributed to the elevated rate performance.…”
Section: Developing High Performance Peo-based Ssbsmentioning
confidence: 99%